2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA ) 2021
DOI: 10.1109/etfa45728.2021.9613416
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Digital Twin for process industry using Apros simulation environment

Abstract: joonas.salmi, iivo.yrjola, jonathan.bensky}(at)aalto.fi, gerardo.santillan(at)semantum.fi, nikolaos.papakonstantinou(at)vtt.fi, seppo.sierla(at)aalto.fi, valeriy.vyatkin(at)aalto.fi

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…This strategy allows the use of an interpretable model (physics-based) to build a fast DT (machine learning) that will be connected to the PO to support real-time engineering decisions. In addition, ref [ 84 ] shows how to build a hybrid DT model of a heater in a water process system. The work details the steps for updating the physical model and process system using data-driven models of the process equipment.…”
Section: Digital Twin Modelingmentioning
confidence: 99%
“…This strategy allows the use of an interpretable model (physics-based) to build a fast DT (machine learning) that will be connected to the PO to support real-time engineering decisions. In addition, ref [ 84 ] shows how to build a hybrid DT model of a heater in a water process system. The work details the steps for updating the physical model and process system using data-driven models of the process equipment.…”
Section: Digital Twin Modelingmentioning
confidence: 99%
“…To make this procedure more automatic, Sierla et al [9] introduced several rules to convert an intermediate graph model into a format suitable for steady state simulation software. Azangoo et al [42] demonstrated how machine learning can extract process parameters for digital twins from recorded process history.…”
Section: Automatic Generation Of Digital Twinsmentioning
confidence: 99%
“…The DT represents the interconnection and convergence between a physical entity and its digital representation, and it can exchange information in real-time in both directions; in this way, the digital entity can control the physical entity and vice versa [10]. There are also hybrid DTs that use a combination of physics-based models, artificial intelligence, and data to create a more accurate tool, which could even be simpler to create if the dynamics are unknown [11]. One of the main reasons for using a DT is that manufacturers can observe in real time the manufacturing/logistics environment, allowing for optimization and cost reduction.…”
Section: Introductionmentioning
confidence: 99%